2021
DOI: 10.3390/ijms22168836
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Inactivation of SARS-CoV-2 on Photoactive AgNPs@TiO2 Ceramic Tiles

Abstract: The current SARS-CoV-2 pandemic causes serious public health, social, and economic issues all over the globe. Surface transmission has been claimed as a possible SARS-CoV-2 infection route, especially in heavy contaminated environmental surfaces, including hospitals and crowded public places. Herein, we studied the deactivation of SARS-CoV-2 on photoactive AgNPs@TiO2 coated on industrial ceramic tiles under dark, UVA, and LED light irradiations. SARS-CoV-2 inactivation is effective under any light/dark conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Several studies have shown that AgNPs can play preventive role against SARS-CoV-2 infection and can contribute to the development of vaccines and virucides based on nanotechnology [ 36 ]. For example, in locations with severe viral or bacterial infections, such as healthcare facilities, nano-silver–modified titanium dioxide is used for self-disinfection of the environment through photocatalysis, thereby preventing the spread of SARS-CoV-2 [ 37 ]. Jeremiah et al evaluated AgNPs with different sizes and concentrations and found that 1–10 ppm of the particles with a diameter of approximately 10 nm could effectively neutralize extracellular SARS-CoV-2, and cytotoxicity was observed at >20 ppm [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that AgNPs can play preventive role against SARS-CoV-2 infection and can contribute to the development of vaccines and virucides based on nanotechnology [ 36 ]. For example, in locations with severe viral or bacterial infections, such as healthcare facilities, nano-silver–modified titanium dioxide is used for self-disinfection of the environment through photocatalysis, thereby preventing the spread of SARS-CoV-2 [ 37 ]. Jeremiah et al evaluated AgNPs with different sizes and concentrations and found that 1–10 ppm of the particles with a diameter of approximately 10 nm could effectively neutralize extracellular SARS-CoV-2, and cytotoxicity was observed at >20 ppm [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies focused on the performances of commercial air sanitizers in eliminating SARS-CoV-2 infected aerosols in indoor spaces [32]. The efficacy of photocatalytic activity against the SARS-CoV-2 virus was demonstrated using industrially coated AgNPs@TiO 2 ceramic tiles irradiated with UV-A [41]. Several studies demonstrated the virucidal activity of ozone against human respiratory viruses, such as Influenza virus [42], Influenza A and respiratory syncytial virus [43], SARS-CoV-1 [44] and other viruses [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, hybrid synthesis approaches may be explored to balance the toxicity (low) and stability (high) properties of AgNPs. Moreover, the silver nanoparticles and nanocomposites are currently recommended by several researchers as a potential antiviral agent to combat coronaviruses [ 18 , 229 – 231 ], which can lead to severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). These new type of viruses can cause acute respiratory distress syndrome (ARDS) and acute lung injury (ALI), which leads to pulmonary failure and/or fatality [ 232 ].…”
Section: Future Perspectivesmentioning
confidence: 99%